2017
DOI: 10.1007/978-3-319-70281-0_9
|View full text |Cite
|
Sign up to set email alerts
|

Education for Sustainable Development: An Exploratory Survey of a Sample of Latin American Higher Education Institutions

Abstract: Education for sustainable development (ESD) is defined as the knowledge and skills 'needed to work and live in a way that safeguards environmental, social and economic wellbeing, both in the present and for future generations'. Skills for sustainable development include critical thinking, creative thinking, systems thinking and leadership. Over the last decades, there has been efforts across the world to embed ESD into the curriculum. In European Union (EU) countries, some higher education have made efforts to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…This finding is consistent with structuration theory and supports other research revealing universities in Australia have demonstrated a propensity toward signification of environmental initiatives [11]. While there is research in other countries suggesting adoption of the TD is perceived positively in the local community [41,42], the comparatively higher adoption of TD in Australia may be reflective of rhetorical and structural distinctiveness in the culture. In general, however, the increasing and worrying evidence of the effects of human-induced climate change is tending to motivate rhetorical shifts, at least, for institutions in most parts of the world.…”
Section: Discussionsupporting
confidence: 89%
“…This finding is consistent with structuration theory and supports other research revealing universities in Australia have demonstrated a propensity toward signification of environmental initiatives [11]. While there is research in other countries suggesting adoption of the TD is perceived positively in the local community [41,42], the comparatively higher adoption of TD in Australia may be reflective of rhetorical and structural distinctiveness in the culture. In general, however, the increasing and worrying evidence of the effects of human-induced climate change is tending to motivate rhetorical shifts, at least, for institutions in most parts of the world.…”
Section: Discussionsupporting
confidence: 89%
“…Whilst in North America, the achievement of SDGs such as SDG 4 has a strong focus on students, participants in South America argue that major attention needs to be paid to educators in higher education. Hernandez et al (2018) concluded that dissemination and implementation of international HEfSD frameworks in Latin America have been slow and sporadic. Although there are some signs to implement HEfSD into curricula in Brazil and Colombia, these practices have not been substantial or have not permeated higher Education institutions' sustainable development strategies per se.…”
Section: Hefsd In the Americas: Targeted Areas And Gapsmentioning
confidence: 99%
“…2.1.3 Peru. Higher education in countries like Peru lacks a system of political frameworks for implementing sustainable development in HEI education programs (Hernandez et al, 2018). Despite this, promoting actions for sustainable development is increasingly a priority within the education sector (Shephard, 2008) and some efforts are gaining ground at Peruvian universities.…”
Section: Education For Sustainable Development In Higher Education Institutions In Colombia Brazil and Perumentioning
confidence: 99%
“…As some commentators have indicated, examples of ESD integration into curricula and academic literature are heavily biased toward European and North American perspectives. There is a clear absence of documentation which focuses on LA contexts (Blanco-Portela et al, 2018;Hern andez-Diaz et al, 2021;Hernandez et al, 2018;Leal Filho et al, 2018;Malheiros, 2019;Salvia and Brandli, 2021). A cursory review of Latin American (LA) HEIs indicates that these organizations have had rather a slow uptake of sustainable development in their teaching and research agendas-particularly in a comprehensive way.…”
Section: Introductionmentioning
confidence: 99%